Economic, Social and Political Situation of Termez in the Emirate of Bukhara in the Early Xx Century - Abdurashidov Anvar Abdurashidovich (International Journal on Human-Computing Studies, 2022)
these article analyses exact changes to expand the cotton raw material in Southern Uzbeksitan in the XX century. This article glances development of new irrigation systems and study of water resources to expand irrigated lands.